Hashtag for humanity: Analyzing #alleyesonrafah movement on social media - Wiyani , Amanina Rasyid; Yasin, Irfan Ahmad; Qoirunnisa, Fentika Zahra; Munarun, Ahmad; Mustofa, Mahmud Yunus (Jurnal Sosiologi Dialektika, 2025)
The humanitarian conflict between Israel and Palestine has spread not only to the real world but also to the virtual world. This research analyzes the #alleyesonrafah movement on social media as a form of global awareness campaign regarding the situation in Rafah, an area in Palestine that is the last line of protection for residents. Through a digital ethnography based on a content analysis approach, this research explores how hashtag is used by social media users to disseminate information, build transnational solidarity, and mobilize support. Data is collected from platforms such as Twitter, Instagram, and Facebook, with a focus on the frequency of use of hashtags, types of content shared, and interaction patterns among users. The research results show that the #alleyesonrafah movement has successfully attracted global attention, especially through humanitarian narratives spread by activists, non-governmental organizations, and the general public. This study also reveals the important role of social media as a medium for minority voices and driving social change. The #alleyesonrafah movement has demonstrated the profound power of social media as a tool for raising global awareness and fostering transnational solidarity in the face of humanitarian crises. However, this is only the beginning of understanding the complex interplay between digital activism and real-world impact. To build on this foundation, future research should adopt a multi-dimensional approach that explores not only the immediate effects of hashtag-driven campaigns but also their long-term implications, ethical considerations, and broader societal influences.